2017
DOI: 10.1111/nph.14549
|View full text |Cite
|
Sign up to set email alerts
|

The δ18O and δ2H of water in the leaf growth‐and‐differentiation zone of grasses is close to source water in both humid and dry atmospheres

Abstract: The oxygen and hydrogen isotope composition of water in the leaf growth-and-differentiation zone, LGDZ, (δ O , δ H ) of grasses influences the isotopic composition of leaf cellulose (oxygen) and wax (hydrogen) - important for understanding (paleo)environmental and physiological information contained in these biological archives - but is presently unknown. This work determined δ O and δ H , O- and H-enrichment of LGDZ (∆ O and ∆ H ), and the O- and H-enrichment of leaf blade water (∆ O ∆ H ) in two C and three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 57 publications
7
51
1
Order By: Relevance
“…Furthermore, it was recently shown that VPD has no effect on the oxygen isotope composition of water in the leaf‐growth‐and‐differentiation zone (Liu et al . ) where leaf cellulose deposition occurs. These relationships indicate very strongly that the large change of δ 18 O Cel observed in the youngest leaves of transferred plants resulted from the VPD effect on ∆ 18 O LW in the new VPD environment, and the associated effect on the oxygen isotope composition of new photosynthetic products (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, it was recently shown that VPD has no effect on the oxygen isotope composition of water in the leaf‐growth‐and‐differentiation zone (Liu et al . ) where leaf cellulose deposition occurs. These relationships indicate very strongly that the large change of δ 18 O Cel observed in the youngest leaves of transferred plants resulted from the VPD effect on ∆ 18 O LW in the new VPD environment, and the associated effect on the oxygen isotope composition of new photosynthetic products (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the δ 18 O of CO 2 in the growth chamberwhich differed between CO 2 sourceshad no effect on Δ 18 O Cel , as had already been established by DeNiro & Epstein (1979) and Liu et al (2016), as all oxygen in cellulose derives from water (DeNiro & Epstein 1979;Barbour 2007). Furthermore, it was recently shown that VPD has no effect on the oxygen isotope composition of water in the leaf-growth-anddifferentiation zone (Liu et al 2017) where leaf cellulose deposition occurs. These relationships indicate very strongly that the large change of δ 18 O Cel observed in the youngest leaves of transferred plants resulted from the VPD effect on Δ 18 O LW in the new VPD environment, and the associated effect on the oxygen isotope composition of new photosynthetic products (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The outer sheathes of older leaves were removed for all samples to mitigate contributions from that evaporatively enriched (in 2 H and 18 O) material. 13,14 This plant portion was selected for its lower MeOH and EtOH content. 1 We sought to utilize an analyte source that would inherently have limited spectral contamination issues.…”
mentioning
confidence: 99%